Comparative Study on Knowledge and Awareness of Common Ocular Diseases Among Rural and Urban Community in Siraha District of Nepal: The Lahan Study - Sahu, Sabin; Karn, Rajiv Ranjan; Ram, Dipesh; Malla, Tejsu; Chaudhary, Sanjib; Singh, Sanjay Kumar (Nepalese Journal of Ophthalmology, 2021)
Introduction: Awareness and knowledge about the common ocular conditions can help people to seek early eye care services. The understanding and acceptance of the importance of routine eye examinations can help in timely detection and treatment of the eye diseases and thus help to reduce the burden of avoidable ocular blindness from the general population. Objective: This study aims to assess and analyze the information related to knowledge and awareness of common ocular diseases and eye health among the rural and urban communities of the Siraha district, Nepal. Materials and methods: A descriptive cross-sectional study was conducted between April and June 2018 in Lahan Municipality ward number 6 (urban) and Sakhuwa Nankarkatti Rural Municipality ward number 4 (rural) in Siraha district. The sample size of 975 was calculated from study population of 3247. A systematic random sampling technique was used to interview adults above 18 years of age, using a pre-tested structured questionnaire. The collected data was analyzed. Results: Out of total 975 participants, 514 (52.7%) were from rural community in Sakhuwa Rural Municipality and 461 (47.3%) were from urban community in Lahan Municipality. The mean age was 38.38 ± 15 years. Female participants were more (63.2%) compared to male (36.8%). Overall, 58.3% were literate and 41.7% were illiterate. Rural community had more uneducated participants (48%) compared to urban community (34%). In rural community, 69% were aware about cataract, 83% had knowledge about its treatment; while in urban community 81% were aware about cataract and 86% had knowledge about its treatment. The awareness of glaucoma among the participants was poor, more so in rural cohort (15%) than the urban cohort (25%). The knowledge of glaucoma was 14% in rural and 62% in urban cohort. Awareness that diabetes can affect the eye was found to be significantly lower (p = 0.01) in rural population (25%) compared to that in urban population (41%) in this study. The knowledge about diabetic retinopathy was lower in rural community (38%) compared to urban community (49%). Awareness about Night Blindness was lesser in rural (62%) compared to urban (70%) community (p = 0.17). Awareness about refractive errors were 37% in rural compared to 60% in urban community. The major sources of information were society and eye hospital in both community. Conclusion: The knowledge and awareness level regarding common ocular diseases was high among the community people of urban community (Lahan) in comparison to rural community (Sakhuwa Nankarkatti). Awareness and knowledge level mainly regarding glaucoma and diabetic retinopathy was very poor in both urban and rural community. There is need to conduct comprehensive awareness programs on common ocular diseases like cataract, glaucoma, diabetic retinopathy, night blindness, congenital eye disease, ocular trauma, eye donations and others in both rural and urban areas to raise the awareness level and improve attitudes and right practices reducing the burden of avoidable blindness.